Estudo do indicador de queima de biomassa levoglucosano em sedimentos de fundo da região do Baixo Rio Negro, Amazonas - Santos, Caroline de Jesus (Brasil, 2024)
The Rio Negro, the focal point of this study, is one of the main bodies of water that flows into the right bank of the Amazon River basin, and has unique characteristics that make it necessary to carry out a more detailed investigation into the composition of molecular markers in its environment. Unlike other markers such as black carbon or polycyclic aromatic hydrocarbons, levoglucosan is specific to biomass burning and does not occur naturally in sediments. The aim of this study was therefore to investigate the presence of levoglucosan in bottom sediments, since there are few studies that have used this matrix for analysis and no record of previous investigations with this matrix in the study region in question. For the analysis of levoglucosan in bottom sediments, the following steps were carried out: extraction with the addition of ((1S)-(+)-ketopinic acid (KPA) to analyze the efficiency of the method, filtration, concentration by low flow of an inert gas (N2), derivatization with (N, O-bis(trimethylsilyl)trifluoroacetamide) (BSTFA) and pyridine, and then analyzed by gas chromatography coupled to mass spectrometry (GC-MS) using Trace GC Ultra equipment, coupled to Thermo Scientific's ISQ Single Quadrupole MS spectrometer, using a ZB-5/MS capillary column (30m × 0.25 mm × 0.25μm). This technique enabled the separation and identification of the compound in samples of bottom sediments collected in the Lower Rio Negro region, Amazonas, in November 2023, during a period of extreme drought, as well as the presence of a lot of smoke due to the increase in forest fires in this region.